Neurophysiological mechanisms underlying the modulation of cognitive control by simultaneous conflicts. (June 2019) - Chmielewski, Witold X.; Beste, Christian
Abstract: Acting adequately in a given situation is complicated by the presence of ambiguous information. Being able to overcome such conflicts is a necessary prerequisite in everyday life, because it enables goal-directed behavior. On a conceptual level, different kinds of conflict can be distinguished: conflicts at a stimulus level (S-S conflicts) can be dissociated from stimulus-response (S-R) conflicts. Considering cognitive psychological frameworks, we examined whether simultaneously presented conflicts potentiate each other, or are rather integrated into a single conflict. To assess the neurophysiological mechanisms and functional neuroanatomical structures that are modulated by independent, interfering or integrative processing of conflicts, we use a Simon-Stroop paradigm in combination with EEG recordings and source localization. We show that S-R (Simon) conflict monitoring processes reflected by anterior cingulate cortex (ACC) and N2 ERP component modulations are unaffected by simultaneous S-S (Stroop) conflicts. In contrast to that, S-S (Stroop) conflicts, reflected in N450 ERP component and ACC modulations are not processed separately when there is an already existing S-R conflict. Rather, S-S (Stroop) conflicts are likely integrated into previously established S-R conflict resolution and also modulate response selection processes associated with the modulation of the P3 ERP component and dorsolateral prefrontal structures. The results suggest that even though different kinds of conflicts can be distinguished, they can become integrated during neural processing associated with medial frontal areas.